POLYPHONY IN THE WORKS OF STOJAN STOJKOV CREATED BETWEEN 1960 AND 1980 - Jovikj, Tihomir (University "Ss. Cyril and Methodius", Faculty of Dramatic Arts, 2019)
Stojan Stojkov (village of Podaresh, Radovish, October 17, 1941) is one of the most prominent Macedonian musicians. His compositional opus covers works of various genres, works that arise primarily from the Macedonian folklore and spiritual tradition. The aim of the paper is to elaborate the author's approach to the polyphonic syllable, one of the basic, traditional principles of the organization of music matter. In particular, the research is aimed at determining the type, manner and scope of the use of polyphony in the work of Stojan Stojkov created in the period from 1960 to 1980. For this purpose, a corpus of available works (scores and recordings) of the author's opus created during the abovementioned twenty-year period is formed. In doing so, the following isues have been considered: original works, works that represent folklore and music for children. The analysis of the works is done according to the standard procedures used in the analysis of polyphonic works.
Keywords: works, musical forms, syllable, polyphony, tradition.